KONTROVERSI MASHLAHAH PERSPEKTIF NAJM AL-DIN AL-THUFI AL-HANBALI - A. Malthuf Siroj (JURNAL AT-TURAS, 2015)
Najm al-Din al-Thufi al-Hanbali is a smart, intelligent, productive and brave Islamic Scholars. He was considered as controversial person among his colleagues, because of his views on mashlahah are different from the other scholars of Usul -Fiqh in general. He said that the most important sources of Islamic law are the texts (Al-Quran and Al-Sunnah). It is no problem if both are relevant with mashlahah. However, if they contradict the mashlahah, the solutions that can be taken is prioritizing mashlahah of texts by specification(takhsis), not eliminating texts . At this point Thufi’s thought is considered as controversy. This article will attempt to examine this controversy using argumentative and philosophical approach to be able to point it objectively not tendentiously.